DEVELOPMENT OF A TECHNOLOGY FOR OBTAINING A PROBIOTIC STRAIN LACTOBACILLUS BULGARICUS C-2, PROMISING FOR THE PRODUCTION OF STARTER CULTURES AND BIOLOGICALLY ACTIVE ADDITIVES - Khassenova, A.; Shybayeva , A.; Alzhanova , G.; Imamuratova , N. (Eurasian Journal of Applied Biotechnology, 2023)
Lactic acid probiotic bacteria can be widely used for the prevention and treatment of patients with various diseases, such as acute and chronic diseases of the gastrointestinal tract, respiratory tract, to restore intestinal microbiocenosis, in combination with antibiotic therapy. The form of intake of these microorganisms is diverse: fermented milk products, drugs, dietary supplements. In the production of lactic acid starters, including the probiotic strain Lactobacillus bulgaricus, there are problems in the selection of nutrient media and conditions for deep cultivation, the selection of methods and conditions for concentration, and the selection of cryoprotectants for freeze drying. This article presents all the data for the production of the Lactobacillus bulgaricus C-2 strain in powder form with the maximum yield of microorganism cells, promising for introduction into the composition of starter cultures for the dairy industry and into biologically active additives with a probiotic effect. The Lactobacillus bulgaricus C-2 strain was isolated from koumiss and stored in the collection of the branch of the Republican State Enterprise on the REM of the Ministry of Health of the Republic of Kazakhstan "National Center for Biotechnology" in Stepnogorsk. The production nutrient medium, conditions for deep cultivation, methods and conditions of concentration were selected, optimal cryoprotectants for freeze-drying were selected.